Novel scaffold platforms for simultaneous induction osteogenesis and angiogenesis in bone tissue engineering: a cutting-edge approach - Arezoo Saberi; Maryam Kouhjani; Marzieh Mohammadi; Leticia Hosta-Rigau (Journal of Nanobiotechnology, 2023)
Abstract Despite the recent advances in the development of bone graft substitutes, treatment of critical size bone defects continues to be a significant challenge, especially in the elderly population. A current approach to overcome this challenge involves the creation of bone-mimicking scaffolds that can simultaneously promote osteogenesis and angiogenesis. In this context, incorporating multiple bioactive agents like growth factors, genes, and small molecules into these scaffolds has emerged as a promising strategy. To incorporate such agents, researchers have developed scaffolds incorporating nanoparticles, including nanoparticulate carriers, inorganic nanoparticles, and exosomes. Current paper provides a summary of the latest advancements in using various bioactive agents, drugs, and cells to synergistically promote osteogenesis and angiogenesis in bone-mimetic scaffolds. It also discusses scaffold design properties aimed at maximizing the synergistic effects of osteogenesis and angiogenesis, various innovative fabrication strategies, and ongoing clinical studies. Graphical Abstract